MEPHI’S EXPERIENCE IN FORMATION OF PERSONNEL RESERVE PARTICIPANTS - V. D. KOLYCHEV; T. V. BELYAEVA; Yu. A. BRONNIKOVA (Высшее образование в России)
This paper highlights NRNU MEPHI’s experience of involvement of employees in project-oriented forms of activities and also in University program for increasing its competitiveness by the means of effective team building and orientation on the result attainment. The authors consider the system of personnel reserve formation at the University based on the best practices of successful companies, in particular the state atomic energy corporation Rosatom. Achievement of results and task solving by the participants of personnel reserve are possible due to formation of a pool of highpotential employees and the development of the competences necessary for NRNU MEPhI for the solution of perspective tasks of change management, organizational design, structural development and efficiency management. Personnel reserve is viewed as a competitive advantage of the University within the Program of competitiveness.